Is Routine Voiding Cystourethrogram Necessary Following Endoscopic Subureteral Injection for Primary Low-Grade Vesicoureteral Reflux? - Jun-Koo Kang; Min Ji Park; Min Hyun Cho; Jun Nyung Lee (Urogenital Tract Infection)
Purpose An endoscopic subureteral injection (EI) using a bulking agent is a highly successful surgical procedure, particularly for low-grade vesicoureteral reflux (VUR). Despite the serious adverse effects, routine voiding cystourethrogram (VCUG) to determine radiographic success after EI remains controversial. This study evaluated the necessity of routine postoperative VCUG in children with primary low-grade VUR. Materials and Methods From January 2016 to August 2021, children who underwent EI for primary low-grade (I-III) VUR with a history of febrile urinary tract infection (fUTI) were analyzed retrospectively. From January 2016 to July 2018, routine VCUG following EI was performed on all children. Thereafter, postoperative VCUG was performed only if indicated. Clinical success was defined as no fUTI during a 12-month follow-up, and radiographic success was defined as the disappearance of VUR on postoperative VCUG. The clinical and radiographic outcomes in both groups were compared. Results Thirty-six children were analyzed in this study. Three children (8.3%) experienced postoperative fUTI. In the routine group, clinical and radiographic success was observed in 16/17 (94.1%) and 15/17 (88.2%), respectively. Two children in the routine group experienced radiographic failure. Among these, one child showed clinical success, and the other underwent additional EI due to clinical failure. Of the indicated group, clinical failure was observed in 2/19 (10.5%). Of them, persistent VUR was identified in one child. Conclusions Clinical and radiologic success after EI for primary low-grade VUR is high, and routine VCUG for confirming radiographic success has a limited impact on the clinical course.